(untitled) (Research, Society and Development, 2022)
Aim: To describe the epidemiological profile of people affected by leprosy in the Northeast region of Brazil. Methods: Ecological, descriptive, retrospective study, resulting from the analysis of secondary data on leprosy recorded in the Northeast region in the period from 2013 to 2017. Data were obtained from the Computerized Data System of Leprosy Notifications (DATASUS) and Information System of Grievances Notification (SINAN). The absolute frequency, incidence rate, prevalence and Annual Increment Rate (TIA) were calculated (p ≤ 0.05). Results: During the analyzed period, 180,019 new leprosy cases were diagnosed in Brazil, and the Northeast region showed 77,669 new cases, representing 43.13% of the total. Regarding the profile of affected individuals, most are male and aged between 30 and 49 years. The Virchowian form was more prevalent in Maranhão (55.8%) and Dimorpha in Bahia (34.7%) and Pernambuco (34.3%). Regarding the TIA, in the states of the Northeast region, there is stability in the prevalence rates for Pernambuco and Bahia, and a decrease in Maranhão. Conclusion: The three analyzed states did not meet the targets for new cases reduction, as well as reduction in Degree II cases. The sociodemographic variables of patients indicate the prevalence of socioeconomic inequalities that impact patient’s life quality. This investigation may contribute to the development of public policies to improve health conditions of the affected population and highlights the need of further studies that deepen the investigation in Maranhão, which shows the high rates for this disease.